2015
DOI: 10.1016/j.iac.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Inner City Asthma

Abstract: SYNOPSIS The inner city has long been recognized as an area of high asthma morbidity and mortality. A wide range of factors interact to create this environment. These factors include well-recognized asthma risk factors that are not specific to the inner city, the structure and delivery of health care, the location and function of the urban environment, and social inequities. This article will review these facets and discuss successful and unsuccessful interventions in order to understand what is needed to solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 92 publications
(92 reference statements)
1
27
0
Order By: Relevance
“…The prevalence of asthma in the United States has increased from 7.3% in 2001 to 8.4% in 2010 (2). Currently, asthma affects over 300 million people and one out of every 250 deaths worldwide is attributed to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of asthma in the United States has increased from 7.3% in 2001 to 8.4% in 2010 (2). Currently, asthma affects over 300 million people and one out of every 250 deaths worldwide is attributed to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…These and more recent studies have further identified cockroach allergens as one of the strongest risk factors for allergic sensitization and asthma morbidity in low-income, urban populations [86, 118122]. Although some investigations have suggested that mouse allergen may be more clinically important in these populations [53•, 123], co-exposure to both allergens is common, and more than 50% of urban children with asthma are sensitized to one or the other [119].…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%
“…In the United States, 21.2% in Mexican Americans, 24.3% in non-Hispanic blacks, and 14% in non-Hispanic whites are obese [58]. Interestingly, worse asthma control is uniformly associated with increased body mass index in boys.…”
Section: Obesitymentioning
confidence: 99%
“…Obviously, effects of ethnicity might be confounded with those effects associated with low socioeconomic status. Lower-income, minority communities have higher exposures to environmental pollutants because of the disproportionately higher numbers of toxic waste dumps, major highways, bus terminals, industry, and so forth located nearby [58]. In USA, being a member of a racial/ethnic minority group (non-Hispanic black 4.4%, Hispanic 5%, non-Hispanic white 3.1%), being foreign born (5.1 vs 3.5% native born), and speaking a language other than English at home (Spanish 5.1% vs English 3.3%) increases the probability of living close to a major highway [64].…”
Section: Environmental Factorsmentioning
confidence: 99%